The Effect of Breadfruit Leaves (Artocarpus altilis) Addition to Antioxidant Content and Organoleptic Properties of Ginger Wedang - Triana, Fatimah Agus; Devi, Mazarina; Soekopitojo, Soenar (Universitas Ahmad Dahlan, 2021)
Ginger breadfruit leaves wedang is a functional beverage made from breadfruit leaves that contains high antioxidant value, ginger and palm sugar. Moreover the adding healthy value function in ginger breadfruit leaves wedang product, also to utilizing the breadfruit leaves into functional beverage of ginger breadfruit leaves wedang in order to be accepted by the people. This research aims to know 4%, 5% and 6% breadfruit leaves addition influence to antioxidant content (gallic acid, quercetin and kaempferol) and organoleptic properties. This experiment research using Completely Random Design (CRD) with three kinds of treatment. The analyzed data using One Way ANOVA, if the treatments shows difference significant, then the analyzed data should be proceed by Duncan’s Multiple Range Test with 5% confidence interval. The highest value of gallic acid antioxidant contect leads in 6% ginger breadfruit leaves wedang about 92,326 μg/ml. The highest value of quercetin antioxidant contect leads in 6% ginger breadfruit leaves wedang about 36,767 μg/ml. The highest value of kaempferol antioxidant contect leads in 6% ginger breadfruit leaves wedang about 25,921 μg/ml. The highest score of color hedonic is 3,97, and the highest score of taste hedonic is 3,67. The highest score of color hedonic quality is 3,11 with dark brown color criteria. The highest score of taste hedonic quality is 4,17 with a bit bittersweet taste criteria